1997
DOI: 10.1002/(sici)1520-636x(1997)9:5/6<616::aid-chir32>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Absolute configurational assignment of self‐organizing asymmetric tripodal ligand‐metal complexes

Abstract: The solution configuration of labile coordination complexes may be difficult to determine, even in cases in which the solid state structure is known. We have previously synthesized a series of chiral ligands which form pseudo-C 3 -symmetric complexes with Zn II and Cu II salts that possess an available electrophilic coordination site. Molecular modeling of Zn II complexes of the chiral ligand N,N-bis[(2-quinolyl)methyl]-1-(2-pyridyl)ethanamine (␣-MeBQPA) showed that the spatial arrangement of the heterocyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 25 publications
3
45
0
Order By: Relevance
“…We have further extended the study to the Cu(II) and Zn(II) complexes of tetradentate N 4 -tripodal ligands related to a-substituted tris ( 16,17 that the complexes under consideration here predominantly display trigonal bipyramidal (tbp) geometry with the pyridine or quinoline moieties binding to the metal ion as monodentate ligands. The pyridine or quinoline chromophores in the complexes adopt the propeller-like arrangement that resembles the structure of the corresponding cis bis-and tris-bipyridyl octahedral complexes.…”
Section: Introductionmentioning
confidence: 99%
“…We have further extended the study to the Cu(II) and Zn(II) complexes of tetradentate N 4 -tripodal ligands related to a-substituted tris ( 16,17 that the complexes under consideration here predominantly display trigonal bipyramidal (tbp) geometry with the pyridine or quinoline moieties binding to the metal ion as monodentate ligands. The pyridine or quinoline chromophores in the complexes adopt the propeller-like arrangement that resembles the structure of the corresponding cis bis-and tris-bipyridyl octahedral complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the related complex [Cu II ((R)-3)(CH 3 CN)](O 2 CF 3 ) 2 was previously established by X-ray crystallography ( Figure 5), circular dichroism, UV/Vis spectroscopy, and elemental analysis. [9] The complex showed a trigonal bipyramidal (tbp) coordination geometry for the metal ion in the solid state; the solution spectra were consistent with this assignment. When the metal ion is tbp, the ligand adopts a C 3 conformation, which orients the two quinoline moieties in a highly asymmetric manner, with projection angle of 128.…”
Section: Resultsmentioning
confidence: 59%
“…[8] From the CD spectra of the complexes we assigned the absolute sense of the orientation of the quinoline rings in solution. [9] Complexes of several metal ions were studied; it was found that only metals that bind the ligand in a trigonal bipyramidal coordination geometry (Zn II , Cu II ) engendered a C 3 -like conformation ( Figure 2) in the ligand and thus gave the propeller twist and large CD amplitudes. Metal ions forming octahedral complexes with 3 (Fe II , Cd II ) enforced a distorted ligand conformation (C s , Figure 2), no twist, and low amplitude CD spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Solvents were freshly distilled over appropriate drying reagents under a N 2 atmosphere. [16]. The chiral Schiff base ligands were prepared in solution and directly used without further separation (Scheme 1).…”
Section: Starting Materialsmentioning
confidence: 99%